2016
DOI: 10.3341/kjo.2016.30.4.302
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of TNF-α Blocker HL036337 and Its Best Concentration to Inhibit Dry Eye Inflammation

Abstract: PurposeDry eye syndrome is commonly thought of as an inflammatory disease, and we have previously presented data showing the effectiveness of topical TNF-α blocker agents for the treatment of this condition. The purpose of this study was to investigate the effectiveness of the TNF-α blocking agent HL036337 compared to cyclosporine A for the treatment of dry eye induced inflammation in order to establish whether HL036337 represents a more effective method for suppressing inflammation. The efficacy of HL036337 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…This lack of correlation was unexpected, as the TNF protein is more likely to have a causative role in CFS worsening. 58 While all CsA treatments showed efficacy on CFS, the expression profiles of the inflammatory genes followed in this study tend to indicate that there were some differences in how the CsA-based formulations modulate these inflammatory genes. These differences might result from the difference in CsA concentration found in the three eye drops and from the difference in their vehicle composition too.…”
Section: Discussionmentioning
confidence: 68%
“…This lack of correlation was unexpected, as the TNF protein is more likely to have a causative role in CFS worsening. 58 While all CsA treatments showed efficacy on CFS, the expression profiles of the inflammatory genes followed in this study tend to indicate that there were some differences in how the CsA-based formulations modulate these inflammatory genes. These differences might result from the difference in CsA concentration found in the three eye drops and from the difference in their vehicle composition too.…”
Section: Discussionmentioning
confidence: 68%
“…These indicates that IL-6α and TNF-α are the major factors affecting dry eye related inflammation and LLLT may reduce inflammation through controlling the level of TNF-α in its mechanism. 33,34 TNF-α, one of the most important pro-inflammatory cytokines, is known to be involved in various chemokine productions and the recruitment of macrophages, neutrophils, and T-cells at inflammation site to enhance inflammatory responses. 35 There is still a lack of studies regarding the relationship between LLLT and cytokine levels in ocular inflammation, but some studies on other tissues such as muscle and lung showed that LLLT is effective in reducing TNF-α expression and controlling the degree of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse models, the lacrimal and submandibular glands are the first affected in the disease process, and several inflammatory mediators such as interleukin (IL)-1β, IL-6, IL-17, interferon-γ, TNF-α, chemokine ligand 2, and MMPs have been implicated in DED-associated inflammation 46 . TNF-α, as well known inflammatory cytokine, is involved in immune and inflammatory responses, and recently reported that inhibition of TNF-α can improve DED 47 . We also previously reported that desiccating stress promote the expression of TNF-α in lacrimal gland in NOD.B10.…”
Section: Discussionmentioning
confidence: 99%